(untitled) (REMUNOM, 2026)
This study aimed to evaluate the physicochemical characteristics and vitamin C content of cashew pulp sold in supermarkets in different areas of Teresina, Piauí, Brazil. Four commercial brands, acquired in two distinct batches, were analyzed, totaling eight samples evaluated in triplicate. Determinations of pH, titratable acidity, soluble solids (°Brix), and vitamin C content followed official AOAC (2005) methodologies, with analyses performed at the Bromatology Laboratory of the Federal Institute of Piauí. pH values ​​ranged from 3.24 to 3.51, falling below the minimum established by the Identity and Quality Standards (3.8). This reduction may be associated with the degree of fruit ripeness, technological processes, the addition of acidulants, or storage conditions. Titratable acidity showed wide variation (0.43 to 1.62 g/100 g), highlighting significant differences between brands, possibly related to the raw material used or industrial processing. Soluble solids ranged from 7.07 to 13.1 °Brix, with values ​​below the minimum limit established by current legislation, suggesting dilution, use of less ripe fruits, or inadequacies in processing. Vitamin C content ranged from 130.00 to 246.67 mg/100 g, remaining within the expected range for cashew pulp. The observed difference may be associated with pH, ​​ascorbic acid stability, storage time, and freezing conditions. In general, the results demonstrate high variability among the brands evaluated, indicating a lack of industrial standardization and failures in quality control. It is concluded that some of the samples do not meet the established regulatory parameters, reinforcing the need for greater rigor in production to ensure the quality and safety of cashew pulp sold in the municipality.